دعم التدقيق الداخلي لحوكمة الشركات في مكافحة الفساد –قراءة في تجربة هولندا- - زرقوط, سارة (جامعة الوادي - University of Eloued, 2020)
هدفت هذه الدراسة الى التعرف على ممارسات التدقيق الداخلي والذي يمثل احد ضوابط حوكمة الشركات ، هذه الاخيرة التي تمثل الاداة الاولى لمكافحة ظاهرة الفساد والتي تحول دون تحقيق أهداف التنمية المنشودة ، وتعتبر التجربة الهولندية من التجارب الناجحة في مكافحة الفساد حيث حافظت هولندا على المراتب الأولى طيلة السنوات العشر الأخيرة ، كل هذا في ظل اتباع ضوابط صارمة لتدقيق ونشر القوائم المالية ، الامر الذي يؤدي الى تفعيل الحوكمة على جميع المستويات. وقد تم اعتماد المنهج الوصفي التحليلي من خلال العودة الى المراجع العلمية و المواقع الالكترونية ذات الصلة بمتغيرات الدراسة ، ثم تحليل تجربة هولندا في مجال التدقيق الداخلي كتجربة رائدة يمكن الاستفادة من نتائجها. This study aimed to identify internal auditing practices, which represent one of the corporate governance controls, the latter which represents the first tool for combating the phenomenon of corruption and which prevents the achievement of the desired development goals. The Dutch experience is considered one of the successful experiences in combating corruption as the Netherlands has maintained the first ranks throughout the years. The last ten, all this in light of strict controls for auditing and publishing the financial statements in order to achieve effectiveness governance at all levels. The descriptive and analytical approach was adopted by going back to the scientific references and websites related to the study variables, then analyzing the Netherlands experience in the field of internal auditing as a pioneering experiment that can benefit from its results.
Supporting internal audit of corporate governance in combating corruption - a reading in the Netherlands experience -
مقال
Keywords: التدقيق، التدقيق الداخلي ، حوكمة الشركات ، الفساد